Effectiveness and safety of anakinra in gouty arthritis: A case series and review of the literature - Jeria-Navarro, Sicylle; Gomez-Gomez, Alejandro; Park, Hye Sang; Calvo-Aranda, Enrique; Corominas, Hector; Pou, Maria Antonia; Diaz-Torne, Cesar (Frontiers in Medicine, 2023)
Background Gout is the most common type of inflammatory arthritis. Nonsteroidal anti-inflammatory drugs, corticosteroids, and colchicine are the first-line agents, although they are contraindicated in many patients. Blockade of IL-1 with anakinra can be an alternative. Objective To present a case series of 10 difficult-to-treat gout patients treated with anakinra and perform a scoping review of the effectiveness and safety of anakinra in gout patients. Methods A total of 1,519 citations were screened. The reviewers ran a two-stage screening process by title/abstract and full-text reading. Thirty-eight articles finally met the selection criteria and were included for data extraction and synthesis. Experience in difficult-to treat and complex clinical scenarios, such as active infection, hemodialysis, and transplantation, were specifically described. Results The study sample comprised 551 patients, from whom 648 flares were finally analyzed. The mean age was 57.9 years, and 82.9% were men. The clinical presentation was polyarticular in 47.5% and tophaceous in 66.9%. Sixty-five patients with an active infection, 41 transplanted patients and 14 in haemodyalisis treated with anakinra are described. More than half of the patients had >1 associated comorbidity. Anakinra was effective both for flares (94%) and for long-term treatment (91%) and well tolerated. In the case of flares, 34 (6.7%) adverse effects were registered. Adverse events were more prevalent in long-term treatment. Conclusion Anakinra was effective and safe for management of gout flares in difficult-to-treat patients. It has been used in multiple complex scenarios, such as active infections, dialysis, transplantation, chronic kidney disease, and polyarticular gout. Anakinra has also proven effective as long-term treatment, although there are more concerns about its safety.